The Effect of Fly Ash Nagan Raya on Geopolymer Mortar - Aulia Rachman; Amir Fauzi; Muhammad Azhari; Khairul Amna; Mhd. Arief Diana; Lidya Rosnita (SAINTIS Publishing, 2025)
Industrial waste containing silica (Si), alumina (Al), and calcium (Ca) has potential as an alternative binder in concrete. These compounds form C-S-H and C-A-H gels in water-based systems, or Si-O-Si, Si-O-Al, N-A-S-H, and C-A-S-H gels in alkali-based geopolymer systems, enhancing strength and influencing setting time. One example is investigate FA from Nagan Raya (FANR) Coal-Fired Power Plantation in Aceh. This study evaluates its performance in geopolymer mortar through chemical and mechanical analysis. FANR is rich in Si and Al, improving mortar strength, while Ca content affects binding time. XRD analysis revealed crystalline phases in FANR and geopolymer binders, resulting in low reactivity. SEM analysis showed spherical particles with foggy surfaces, differing from typical glassy fly ash, which influences workability and alkali absorption. Mortar tests indicated the best performance at 8M NaOH and a Na₂SiO₃/NaOH ratio of 3.0, achieving 18.30 MPa compressive strength at 28 days. Higher alkali concentrations increased viscosity, reducing workability and final strength. Overall, FANR shows promise as a geopolymer binder with proper optimization of activator ratios.